Information Gap in teaching speaking - Rini Venta Almira; Zulfadli A Aziz; Nira Erdiana (Universitas Syiah Kuala, 2017)
This study aims at examining whether or not the use of information gap technique can improve students’ performance in English speaking ability and helps teachers in teaching speaking. In order to cope the problems faced by the students in learning speaking, the experimental of pre-test and post-test design was undertaken. The instrument used to collect the data in this study was a set of test. The collected data were analyzed by using descriptive statistic formula. The result of the test was analyzed by using speaking criteria suggested by Brown (2001). From the result of the study it reveals that the result of post-test is higher than the result of pre-test after the information gap technique was applied. It shows that the implementation of information gap can give a significant improvement to the students. It explicitly means that information gap can be one of alternative techniques used by teacher in teaching English particularly in teaching speaking in junior high schools.